Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan (Studi Pada Pt. Bank Rakyat Indonesia Tbk. Tahun 2013-2015) - UTAMI, ETIS PUTRI; Drs. Agus Muqorrobin, M.M (2017)
The purpose of the research is to recognize PT. Bank Rakyat Indonesia Tbk. financial rat io's condit ion. Samples are PT. Bank Rakyat Indonesia Tbk. financial reports in forms of balance sheets and profit and loss reports on 20132015. Data's analysis result s in : 1) Liquidity Ratio Cash Ratio was on the liquid condition so that bank could settled its debts using its treasury available on company's assets. 2) Solvabilit y Ratio Debt to Equity Ratio (DER) was in a good condition upon correcting its performance and can be declared fit due to the descent of DER. 3) Profitability Ratio Return On Assets (ROA) had passed the minimum level and was in a good rank or stated productive. From the whole results of ratio's analysis on 2013-2015, it showed the bank's financial's performance in form of company's profits was in a good condit ion. Keywords : Liquidity Ratio, Solvability Ratio and Profitability Ratio.